2019
DOI: 10.1101/666230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serological and metagenomic interrogation of cerebrospinal fluid implicates enteroviruses in pediatric acute flaccid myelitis

Abstract: BackgroundSince 2014, the United States has experienced a biennial spike in pediatric acute flaccid myelitis (AFM). Epidemiologic evidence suggests non-polio enteroviruses (EVs) are a potential etiology, yet EV RNA is rarely detected in cerebrospinal fluid (CSF) and only inconsistently identified from the respiratory tract, serum, or stool.MethodsWe interrogated CSF from children with AFM (n=42) and pediatric controls with other neurologic diseases (OND) (n=58). Samples were incubated with T7 bacteriophage exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…flaviviruses), one could determine the infection by analysing specific antibodies, which can be detected for a much longer time after infection. Recently, micro arrays containing epitopes to all known human viruses or even the entire human epitome have been developed [26], which allow for the detection of all viruses at once. Nonetheless, detection of (the genome of) a pathogen is often preferred, as serological assays often lack diagnostic accuracy because of high cross reactivity and ambiguous cut off criteria.…”
Section: Discussionmentioning
confidence: 99%
“…flaviviruses), one could determine the infection by analysing specific antibodies, which can be detected for a much longer time after infection. Recently, micro arrays containing epitopes to all known human viruses or even the entire human epitome have been developed [26], which allow for the detection of all viruses at once. Nonetheless, detection of (the genome of) a pathogen is often preferred, as serological assays often lack diagnostic accuracy because of high cross reactivity and ambiguous cut off criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although detection of a pathogen in the CSF would provide definitive proof of causation, in this study and others, no pathogen has been consistently identified in CSF from AFM cases, even with the use of highly sensitive unbiased research technologies for pathogen detection and discovery. 1,19 Development of intrathecal enterovirus antibody tests for CSF may further facilitate diagnosis of enterovirus-associated AFM, 20 even when the virus is no longer present in CSF, similar to diagnosis of neuroinvasive arboviral infections. Additionally, improving AFM awareness to ensure early diagnosis with prompt and complete specimen collection (including respiratory sampling in addition to CSF and stool) will improve the potential for pathogen detection, as evidenced by increased detection rates from specimens collected within 5 days of prodromal symptom onset.…”
mentioning
confidence: 99%